Antibiotic-loaded, silver core-embedded mesoporous silica nanovehicles as a synergistic antibacterial agent for the treatment of drug-resistant infections. (September 2016) - Wang, Yao; Ding, Xiali; Chen, Yuan; Guo, Mingquan; Zhang, Yan; Guo, Xiaokui; Gu, Hongchen
Abstract: Drug-resistant bacterial infections have become one of the most serious risks in public health as they make the conventional antibiotics less efficient. There is an urgent need for developing new generations of antibacterial agents in this field. In this work, a nanoplatform of LEVO-loaded and silver core-embedded mesoporous silica nanovehicles (Ag@MSNs@LEVO) is demonstrated as a synergistic antibacterial agent for the treatment of drug-resistant infections both in vitro and in vivo. The combination of the inner Ag core and the loaded antibiotic drug in mesopores endows the single-particle nanoplatform with a synergistic effect on killing the drug-resistant bacteria. The nanoplatform of Ag@MSNs@LEVO exhibits superior antibacterial activity to LEVO-loaded MSNs (MSNs@LEVO) and silver core-embedded MSNs (Ag@MSNs) in vitro. In the in vivo acute peritonitis model, the infected drug-resistant Escherichia coli GN102 in peritoneal cavity of the mice is reduced by nearly three orders of magnitude and the aberrant pathological feature of spleen and peritoneum disappears after treatment with Ag@MSNs@LEVO. Importantly, this nanopaltform renders no obvious toxic side effect to the mice during the tested time. There is no doubt that this study strongly indicates a promising potential of Ag@MSNs@LEVO as a synergistic and safety therapy tool for the clinical drug-resistant infections.